The Use of Bacteriophage for Detection and Biocontrol of Foodborne Pathogen - Tati Ariyanti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Bacteriophages are viruses that have ability to attack bacterial cells in specific receptors, infect, multiply in bacterial cells and eventually lyse bacterial cells. This unique bacteriophage character is highly beneficial because it is harmless to mammalian cells and does not interfere with natural microbes. Bacteriophages are easy to obtain because they are widespread in the environment such as soil, water, animal, and farm waste or food. This paper describes the potential use of bacteriophages to detect pathogen and foodborne pathogen biocontrol. Bacteriophages are very potential to control the growth of pathogenic bacteria both in food industry and environment. Bacteriophages act as antibiotics, detection tool for pathogenic bacteria in the food chain, food biopreservative from pathogen bacteria contamination, and foodborne disease prevention. Although research on bacteriophage in Indonesia has not been widely reported, research on bacteriophage utilization is being carried on.